Simulation, Optimization and Experimental Verification of the Over-Pressure Reflow Soldering Process - Esfandyari, Alireza; Bachy, Bassim; Raithel, Stefan; Syed Khaja, Aarief Hussain; Franke, Jörg (Procedia CIRP, 2017)
The advanced technologies for electronics production and convection based soldering technologies are growing steadily. The enhanced reflow soldering oven with an integrated hyper pneumatic module ensures a void-free solder connection, but it requires design and installation of the process parameters in the oven in order to ensure optimized heat transfer and derive the best energy efficiency performance. This paper presents a simulation model of the thermal soldering process in the over-pressure convection oven by finite element model. This model considers the effect of the complex boundary conditions during the soldering process. A set of experimental tasks were designed to investigate the variations in the temperature profiles at selected points on the surface of the demonstrator. Moreover, the heat transfer coefficient for each thermal profile has been calculated. The simulation model can be used to predict the temperature distribution for the solder materials together with the demonstrator board. The void content in the solder material was investigated by the X-Ray analysis and correlated with the thermal process in the simulation. Hence, the optimized relation between the process set-up parameters in the oven, simulated thermal behavior, and the voids fraction in solder material are studied in detail.
CRIS-Team Scopus Importer:2023-03-07
Keywords: defect analysis; electronics production; Heat transfer simulation; reflow soldering oven